Utilisation of online public relations tools in chemical companies in the Czech Republic - Krejčík, Jan; Lošťáková, Hana; Jelínková, Martina (Univerzita Hradec Králové, 2022)
Effective online marketing communication is one of the basic prerequisites for the company's success in the market. Today, however, it is not only focused on customers, but also on other stakeholders. Most often used for this purpose are digital public relations (PR), the intention of which is to influence public opinion and create a positive image of the company. The aim of the paper is to summarise data from primary research focused on the analysis of websites of chemical manufacturers regarding the current use of digital messages and communication channels in their online public relations. The study was prepared using descriptive statistics tools. The results show that in terms of written forms, companies most often use the news section. Audio-visual content can only rarely be found on the websites. Links to social networks are also not a matter of course on the web. The most frequently presented social networks include Facebook, LinkedIn and Twitter.
Míra využití nástrojů online public relations ve výrobních podnicích chemického průmyslu v ČR
Keywords: online communication; online marketing; digital public relations; online komunikace; online marketing; digitální public relations